The Emerald Hell: Ideological Continuity of the Spatial Opposition Countryside/City in Riberas del Averno - Campos Ocampo, Melvin (2024)
This article analyzes Jaime Fernández Leandro's 2003 novel Riberas del Averno (San José, Editorial de la Universidad Costa Rica) to determine the correlation that the text establishes between the narrated spaces—rural and urban—and the moral character of those who inhabit these spaces. The paper begins by exploring some theoretical features of the police/detective/noir novel in relation to its moral codes. Specifically, it will show that Riberas del Averno draws a spatial border that responds to a particular moral approach, one which opposes rural and urban spatiality. In other words, the novel is part of a Latin American literary and ideological tradition that begins in the 19th century and continues into the 21st century: the Country / City dichotomy and its correlate Civilization / Barbarism. This opposition has favoured the establishment of order and social control in America, based on considering the rural and the urban as antagonistic moral spaces, in which urban civilization offers law and order, while the rural spatiality of nature is the niche of crime, chaos and barbarism.